2012
DOI: 10.4028/www.scientific.net/amm.174-177.1038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corn Stalk Microcrystalline Cellulose on Thermal and Mechanical Properties of Chitosan Composites

Abstract: The biodegradable composite films were prepared from corn stalk microcrystalline cellulose as filler and chitosan as polymeric matrix. The crystallinity, the tensile properties and the thermal properties of the composites were tested. The results show that the tensile properties and thermal properties were improved with the addition of corn stalk microcrystalline cellulose. When corn stalk microcrystalline cellulose account for 10% of the chitosan quality, the initial decomposition and maximum weight loss rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The CS-MCC10 membrane resulted in a rise of σ by 81.01%. This is almost similar to the results discussed by Li et al (2012) 4 that showed an increase of 83.55% with the addition of 10(w/w%) MCC compared to a pure CS membrane. The CS-CMC10 membrane showed the second highest strength with a σ value of 62.22 MPa ± 4.32 MPa.…”
Section: Mechanical Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…The CS-MCC10 membrane resulted in a rise of σ by 81.01%. This is almost similar to the results discussed by Li et al (2012) 4 that showed an increase of 83.55% with the addition of 10(w/w%) MCC compared to a pure CS membrane. The CS-CMC10 membrane showed the second highest strength with a σ value of 62.22 MPa ± 4.32 MPa.…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…Some of these materials are based on polyesters, protein or even polysaccharides 2 . Amongst these materials, chitosan (CS) has gained a large interest in this area [3][4][5] . It is a naturally occurring polysaccharide polymer consisting of glucosamine and N-acetyl glucosamine.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research conducted by Huang et al [5] showed the tensile strength value of chitosanmicrocrystalline cellulose films, and the addition of cellulose microcrystals to chitosan films decreased the value of water vapour permeability. Other studies have shown chitosan-microcrystalline films with high tensile strength values [6][7]. In this work, modifications were made to the chitosan-microcrystal cellulose film with the addition of a new material, quercetin.…”
Section: Introductionmentioning
confidence: 99%